THE INFLUENCE OF BOYBAND RIIZE AS A CELEBRITY ENDORSER ON CONSUMERS’ PURCHASE INTENTION TOWARD ETUDE PRODUCTS - Mutiara, Ni Ketut Sonia; Istiharini (Journal of Social and Economics Research, 2025)
This study aims to explore the influence of celebrity endorser specifically the K-pop group RIIZE and online customer reviews on consumers’ purchase intention toward Etude products, with trust serving as a mediating variable. The research is grounded in the growing importance of digital marketing, where public figures and user-generated content increasingly shape brand perception and buying behavior, especially among younger, social-media-savvy consumers. A quantitative approach was employed using Structural Equation Modeling (SEM) with AMOS 26.0 to analyze data gathered from 370 respondents, most of whom belong to Generation Z. The variables measured in this study include celebrity endorser, online customer review, trust, and purchase intention, using online questionnaires as the data collection method. The results reveal that celebrity endorsement significantly influences both consumer trust and purchase intention. Trust also plays a role in encouraging purchase intention, although it does not significantly mediate the relationship between celebrity endorsement and intention to buy. In contrast, online customer reviews do not show a significant impact, either directly or indirectly, on trust or purchase intention. These insights offer practical implications for marketers to design visually engaging and emotionally resonant strategies that align with the preferences and behaviors of digital-native consumers, especially those from Generation Z.